Antihypertensives in Hypertensive Disorders of Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Hypertension is the most common medical disorder in pregnancy. It complicates about 15% of all pregnancies and is an important cause of maternal and foetal morbidity and mortality. Hypertension is diagnosed from an absolute rise in blood pressure at or above 140/90 mm of Hg. There is general consensus that severe hypertension should receive pharmacological treatment but the value of treating mild hypertension is controversial. The threshold for treatment is 140-150 mm of Hg systolic and/ or 95-100 mm of Hg diastolic to prevent worsening complications of hypertensive mother. Opinions differ as to which is the best antihypertensive during pregnancy. All antihypertensives are either shown or assumed to cross the placenta and reach foetal circulation. While the goal of treatment is to reduce maternal risk, agents selected must be efficacious and safe for the foetus. Methyldopa and labetolol are considered as the first line antihypertensives. As second line therapy, calcium channel blocker, oral hydralazine are recommended. As third line agent, beta-adrenergic blockers are used. For immediate lowering of blood pressure sublingual Nifidipine , parenteral or oral Labetolol, parenteral Hydralazine are used. Atenolol use should probably be avoided in pregnancy because of its association with low birth weight. Both Angiotensin converting enzymes and Angiotensin receptor blockers are fetotoxic and contraindicated during pregnancy. This review article was done with the aim to update knowledge regarding indication, safety, side effects as well as impact of anti-hypertensives on the foetus. DOI: 10.3329/bjog.v23i2.4963 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 65-77